2021
DOI: 10.3174/ajnr.a7258
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian FRED Registry: A Prospective Multicenter Study for Brain Aneurysm Treatment—The BRED Study

Abstract: BACKGROUND AND PURPOSE:The development of flow diverters has changed the endovascular approach to intracranial aneurysms. On the basis of good results, the indications for flow diverters have expanded to include aneurysms of different shapes, locations, and sizes. The objective of the study was to report on the performance of the Flow Re-Direction Endoluminal Device (FRED) in intracranial aneurysm treatment at early and medium-term follow-up. MATERIALS AND METHODS:This single-arm, multicentric, prospective, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Many papers have demonstrated the effectiveness of the FDs. [3][4][5][6][7][8][9] In a systematic review of the FDs, Briganti et al reported that the rate of aneurysm occlusion progressively increased up to 81.5% over a mean follow-up period of 9-months. They also reported the neurologic morbidity within allowance (3.5%), rate of hemorrhagic complication (2.9%), and rate of non-negligible thromboembolic complications (4.1%).…”
Section: Introductionmentioning
confidence: 99%
“…Many papers have demonstrated the effectiveness of the FDs. [3][4][5][6][7][8][9] In a systematic review of the FDs, Briganti et al reported that the rate of aneurysm occlusion progressively increased up to 81.5% over a mean follow-up period of 9-months. They also reported the neurologic morbidity within allowance (3.5%), rate of hemorrhagic complication (2.9%), and rate of non-negligible thromboembolic complications (4.1%).…”
Section: Introductionmentioning
confidence: 99%